Novel phenomena in dilute electron systems in two dimensions - Sarachik, M. P. (The National Academy of Sciences, 1999)
For the past two decades, all two-dimensional systems of electrons were believed to be insulating in the limit of zero temperature. Recent experiments provide evidence for an unexpected transition to a conducting phase at very low electron densities. The nature of this phase is not understood and is currently the focus of intense theoretical and experimental attention.